POLITIK HUKUM DALAM PEMBENTUKAN PERATURAN PRESIDEN NOMOR 7 TAHUN 2018 TENTANG BADAN PEMBINAAN IDEOLOGI PANCASILA - Suratna, Rosyida Wongso; Achmad, Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study aims to examine the legal politics of Presidential Regulation Number 7 Year 2018 concerning the Pancasila Ideology Development Board is reviewed from philosophical, sociological, and juridical aspects. This research is a prescriptive legal research, with a conceptual approach. The legal meterials includes primary and secondary legal materials. The data collection technique used is literature study. The analysis technique used is the deductive method. These results and research indicate that the legal politics of the establishment of Presidential Regulation No. 7 of 2018 concerning the Pancasila Ideology Development Board is a body that was built as a form of Pancasila re-actualization in the process of internalizing values in every component of society and state administrators. BPIP is present as a solution in the midst of a crisis of confidence in the relevance of Pancasila as an ideology and state philosophy. This is in accordance with the nine points of President-Vice President Nawacita especially in items 8 and 9 which are carried out through BPIP technical programs.